"Departure of children from Barcelona, Ministry of Education, to Sitges"(children's colonie). Place of persons indicated on the back. Copied from CNT collection
"Departure of children from Barcelona, Ministry of Education, to Sitges"(children's colonie). Place of persons indicated on the back. Copied from CNT collection.